Implementation of Minimum Exhaustion Criteria Based on Intelligence Quotient (IQ) in Islamic Religious Education Subjects to Increase Student Learning Motivation - Nurjunaedah, Nida; Nurainiyah, Nurainiyah; Nurjanah, Nurjanah; Rusydi, Ibnu (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
The determination of Minimal Completion Criteria (KKM) based on intelligence often equates students with high and low intelligence levels, resulting in students with high IQs feeling bored and saturated due to the lack of targets that align with their intelligence capacity. This study aims to describe the implementation of intelligence-based KKM at Madrasah Aliyah Persatuan Islam Sindangkasih Ciamis, starting from the planning process, implementation, and the results of KKM implementation in Islamic Religious Education (PAI) subjects. The research findings show that: First, the planning for the implementation of IQ-based KKM at Madrasah Aliyah Persatuan Islam Sindangkasih Ciamis involves measuring students' IQ and talents by involving psychological institutions. The results of the IQ measurements are then converted into KKM scores. Second, the implementation of IQ-based KKM involves cooperation between all school stakeholders, including the principal, deputy head of the curriculum field, PAI teachers, BK teachers, and parents, as well as monitoring and evaluating the learning process and student learning outcomes. Evaluation is carried out through formative and summative tests. Some of the obstacles faced include the absence of IQ data for transfer students or those who have not taken the IQ test, as well as issues faced by students in studying that prevent the achievement of the set completion criteria, such as limited infrastructure.